Glycoproteins profiles of placental extract -A step towards development of biomarkers of pregnancy in water buffalo - KUMAR, PRADEEP; SAXENA, ABHISHEK; SINGH, S K; AGARWAL, S K (The Indian Journal of Animal Sciences, 2014)
In this study, profiles of glycoproteins of buffalo cotyledons at different stages of pregnancy were studied. First time, WGA lectin affinity chromatography was used to isolate glycoproteins from cotyledons at different stages of gestation in buffalo. The hyper immune sera against the isolated glycoproteins showed no cross reactivity to non- pregnant tissue extract confirming the presence of glycoproteins in samples associated with pregnancy. During early pregnancy, presence of 4 glycoproteins of molecular weights 86, 67, 56 and 51 kDa and out of these glycoproteins, 3 glycoproteins (67, 56 and 51 kDa) were found immunoreactive on western blot analysis. Five glycoproteins of molecular weights 86, 75, 67, 56 and 38 kDa were identified in the mid- and late- stages of pregnancy and all were found immunoreactive. These glycoproteins may be useful for development of RIA/ ELISA based species specific assay for pregnancy diagnosis and monitoring of fetus in buffalo.